Perkiraan Umur Transformator Berdasarkan Pengaruh Pembebanan Dan Temperatur Lingkungan Menggunakan Metode Trend Linear - Yolla Yaumil Rizki; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Base on overloading conditions and the exposure of ambient temperatures that exceed the standard level, will causes thermal aging of the insulation on the transformator,which can causes “shrinkage” the age of it. Sampling of the transformator that used in this research,is the power transformator. Both of it,have been installed from 2010 (tranformator 3) and 2015 (transformator 4) at major sub-station in Garuda Sakti-Pekanbaru. These tranformators are operated at maksimum ambient temperature 33oC . To estimate the remaining transformators lifespan,can be evaluated by using a hot spot temperature. In this article, estimating the lifetime of the transformators are calculated by using linear trend analysis method,for load escalation of these transformator. The results showed that,all of the transformator have a safe value limit of 91.38% of the transformators power rating level. From the calculation of power transformator 3 has an estimation remaining age around 26 years with the value of forecasting load in 2019 reaching 80.27% until 2024 reaching 113.61% of the power rating. And another tranformator (4) has an estimation remaining age around 21 years with the value of forecasting load in 2019 reaching 75,89% until 2031 reaching 113,09% of the power rating.Keywords : Transformator Lifespan, Trend Linear Method, Load Escalation, Ambient Temperature.